Iman Kepada Allah Dan Nilai-Nilai Maqashidul Qur’an : Studi Tafsir Maqashidi terhadap QS. Thaha Ayat 14 dan QS. Al-Anbiya’ Ayat 25 - anam, khizan ahmilul; Waliko, Waliko; Asani Mustika, Hilda (Tasamuh: Jurnal Studi Islam, 2023)
The purpose of this writing is to express faith in Allah in the Qur'an and to describe its meaning in social life based on the context of the revelation of the verse under the current conditions using the values ​​of Maqashidi interpretation. The main object of this research is faith in Allah in the Qur'an. This research is a type of qualitative data analysis research with data collection methods taken from data in the literature, reading, taking notes and compiling research materials. The results of this study are the results of the author's analysis of QS. Thaha Verse 14 and QS. Al-Anbiya verse 25 with maqashidi interpretation analysis. By paying attention to the values ​​of the maqasid syari'ah and the values ​​of the maqashid al-Qur'an. The result is maqashid from the verse described by the author, namely the obligation to worship as a communication between Allah SWT and humans, as well as the benefits of people who always carry out Allah's commands will always get good things from their deeds, conversely if someone ignores His commands then he will get bad consequences from the amaliyah, in other words faith must also be proven by ihsan or good deeds..